Modern Organoselenium Catalysis: Opportunities and Challenges - Liao, Lihao; Zhao, Xiaodan (Synlett, 2021)
Organoselenium catalysis has attracted increasing interest in recent years. This Cluster highlights recent key advances in this area regarding the functionalization of alkenes, alkynes, and arenes by electrophilic selenium catalysis, selenonium salt catalysis, selenium-based chalcogen-bonding catalysis, and Lewis basic selenium catalysis. These achievements might inspire and help future research.1 Introduction2 Electrophilic Selenium Catalysis3 Selenonium Salt Catalysis4 Selenium-Based Chalcogen-Bond Catalysis5 Lewis Basic Selenide Catalysis6 Conclusion
Keywords: organoselenium catalysis; electrophilic selenium; selenonium salt; chalcogen bonding; Lewis basic selenium